Assessment of computer vision syndrome and associated factors among employees of Ethio-telecom in Addis Ababa, Ethiopia - Natnael Gizachew; Teferi Abegaz; Tenaw Demis; Melese Gashaw; Lidetu Demoze (Frontiers in Public Health)
BackgroundComputer vision syndrome refers to a range of eye and vision-related problems which may result from extended use of digital devices such as computers. It is a public health problem, affecting more than 70% of all computer users. In developing countries like Ethiopia, there is scarcity of studies on computer vision syndrome, particularly in the telecom industry making evidence-based interventions difficult. Hence, the study aims to identify the determinants and the prevalence of computer vision syndrome among Ethio telecom workers in Addis Ababa, Ethiopia.ObjectivesThis study aimed to determine the prevalence of CVS and identify its factors among Ethio telecom workers in Addis Ababa, Ethiopia.MethodsInstitution-based cross-sectional study was conducted among Ethio telecom employees in Addis Ababa, Ethiopia from March to June 2023. A total of 497 individuals participated in the study. Data were collected using an interviewer- administered questionnaire through Kobo Toolbox, observational checklist and an illuminance measuring instrument. The data were transferred to Statistical Package for the Social Sciences (SPSS) version 26 for analysis. Multivariable logistic regression was performed to assess the association and control for potential confounders.ResultsThe prevalence of CVS among Ethio telecom workers was 68.8% (95% CI: 64.5–72.9). Significant associations were observed with viewing distance <50 cm (AOR: 2.32, 95% CI: 1.24–4.33), improper task illumination (AOR: 1.78, 95% CI: 1.09–2.91), habit of taking breaks (AOR: 0.439, 95% CI: 0.281–0.686), and adjustment of brightness and contrast (AOR: 0.39, 95% CI: 0.22–0.68).ConclusionMore than two-thirds of Ethio telecom workers in Addis Ababa suffer from CVS, with significant influences from viewing distance, task illumination, breaks, and monitor settings. These findings underscore the need for interventions to enhance working conditions and reduce CVS prevalence among computer users.